Exploring the potential of assessment efficacy in sports coaching - A Commentary - Reade, I. (International Journal of Sports Science and Coaching, 2012)
Assessment is an essential part of the learning process; Hay et al. and many others have made the case and established the connection. Simply put, assessment enhances learning. The concept of assessment efficacy is well articulated by the authors and convincingly positioned in their writing as beneficial to coach and athlete learning. Learning can and does occur throughout life without assessment, but it is through assessment that we attempt to measure what has been learned with the intent of progressing to higher levels of educational content. It is critical to know the progress being made by the learner, and whether the teaching methods are effective. If a desired outcome of coach education is to progressively develop increasingly competent coaches, is this progression futile in the absence of assessment? In this brief commentary on the article by Hay et al., I concur with the concept of assessment efficacy and focus primarily on the practicality of assessment as fundamental to coach education.